2022
DOI: 10.5502/ijw.v12i2.2019
|View full text |Cite
|
Sign up to set email alerts
|

The comeback effect: How happy are people who have recovered from a COVID-19 infection?

Abstract: There is already a large body of research on the dramatic negative effects of COVID-19 on peoples’ mental and physical health. Millions of people have died, and the pandemic has negatively influenced the lives of billions of people. Luckily however, the vast majority of people infected with the virus, recovers. The happiness and wellbeing of these people have not been extensively studied. In the current paper, we ask the question: Are people who have recovered from a COVID-19 infection happier than those who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The participants were selected from the Novus Sweden Panel, which comprises approximately 50,000 randomly selected panel members. The Novus Sweden Panel has been utilized in various research domains and empirical studies published in international journals (see, e.g., Dahlen et al, 2022; Kennedy et al, 2022; Svedsäter et al, 2021).…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were selected from the Novus Sweden Panel, which comprises approximately 50,000 randomly selected panel members. The Novus Sweden Panel has been utilized in various research domains and empirical studies published in international journals (see, e.g., Dahlen et al, 2022; Kennedy et al, 2022; Svedsäter et al, 2021).…”
Section: Methods and Datamentioning
confidence: 99%
“…This was also evident in Sweden, and by the end of 2020, there was already a significant decline in government support in the Nordic countries, albeit still at somewhat higher levels than before the pandemic (Bengtsson & Brommesson, 2022;OECD, 2021). in various research domains and empirical studies published in international journals (see, e.g., Dahlen et al, 2022;Kennedy et al, 2022;Svedsäter et al, 2021).…”
Section: Government Communication Management and Institutional Trust ...mentioning
confidence: 99%
“…For example, surveys of individuals in both developed and developing countries found that their own assessments of their relative income were not very good predictors of their poverty or wealth [14,24]. Similarly, while objectively on the same level, individuals' assessments of their health have been found to differ between countries [23] and before versus after the COVID pandemic [25]. Even housing needs have been found to differ in manifest versus subjective terms over time [26].…”
Section: Subjective Welfarementioning
confidence: 99%